Kontribusi Sosiologi Terhadap Moderasi Beragama - Muhayat, Imam (Proceedings of Annual Conference for Muslim Scholars, 2019)
Religion in a sociological perspective contains of kindness, nobleness, grandeur, and glory for his folower. Religion (read: Islam) is a religion that was revealed by Allah, brought by the Prophet, Muhammad Saw., with the aim to provide guidance for humans and summarize the realization of welfare for humanity (read: being religious). In other hand, tends to be religious moderation in the position of conceptual categorization. It means being religious on theological essence; and historical-sociological pattern or as a grand cultural phenomenon. Then bring up religious studies from a sociological perspective. Both are related inter-values, norms, meanings, phenomena and all individual interactions relating to the life of groups, communities, and at large societies, presumably can be a starting point in religious life. So that being religious is in the position of the sliced space which contains rules, norms, values, and likes the order found in religion and sociology. Indonesia is not based on Islam as the major religion, but his people are referred as an Islamic society, even if it is not an Islamic state. Islamic society which is meant that the religious product is friendly to science, technology, age, morals and so on.